Structure properties relationship of Pb0.92La0.08(Zr0.4Ti0.6)0.98O3 ceramics - Chumprasert L. (2017)
© 2016 Trans Tech Publications, Switzerland. Structure-property relationship has been performed in the lanthanum-modified lead-zirconate-titanate (PLZT) with a lanthanum content 8 and Zr/Ti ratio 40/60. The X-ray diffraction analysis, scanning electron microscopy, and sintering behavior have evidently demonstrated that it is possible to tailor the structural properties of PLZT 8/40/60. Structure of PLZT 8/40/60 had pure perovskite with tetragonal without secondary phase. Tetragonality (c/a) was observed in the range of 1.01093-1.02095. SEM micrographs were shown a development of mean grain size to clarify the development of grain after sintering processing. The result shows that increasing of sintering temperature resulted in mean grain size increasing from 1.70 to 3.08 μm. Ferroelectricity of PLZT ceramics were normal ferroelectric and dielectric constant increased with the increasing sintering temperature.